(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
An effective healthcare system is achieved when appropriate measures have been taken for the effective treatment of patients. Triage is a process that assists healthcare workers in determining the condition of the patients and arrange appropriate treatment for them (Chong & Gan, 2016). This research aimed to evaluate the awareness and knowledge of healthcare workers in the Emergency Department of the five district hospitals in La Union using the descriptive-evaluative research method. A survey questionnaire was used to gather the data needed in the study, and the five-point Likert scale was utilized to determine the level. This research aimed to evaluate the awareness and knowledge of healthcare workers in the Emergency Department of the five district hospitals in La Union using the descriptive-evaluative research method. A survey questionnaire employing the five-point Likert scale was utilized to determine the level of awareness and practice of healthcare workers. Meanwhile, descriptive and inferential statistics were used to treat the data gathered. The findings revealed that the respondents have a) very high awareness in non-emergency and medico-legal cases; b) high awareness in emergency cases; c) very high knowledge in non-emergency cases; and d) a high knowledge in emergency and medico-legal cases. Meanwhile, there was a significant relationship between the training/ seminars attended by the respondents to the level of awareness and knowledge of the respondents on the emergency triage. Furthermore, a significant relationship also existed between the level of awareness and the knowledge of the respondents; hence, an emergency triage system for healthcare workers was crafted and proposed for adoption by the District Hospitals in La Union through the Provincial Government.